The Relationship Between The Size Of Company And The Systematic Risk Of Accepted Companies In Tehran Stock Exchange - Nahich, Mohammad (2009)
In this research the author try to evaluate the relationship of two variables in decisions. That is, the size of company and the systematic risk in accepted companies in Tehran exchange.